Peningkatan Partisipasi dan Pemahaman Nilai Keagamaan Melalui Implementasi Pendekatan Konstruktivis dalam Desain Pembelajaran PAI di Sekolah Dasar - Dirgantini, Siti Rochmah (Epistemic: Jurnal Ilmiah Pendidikan, 2023)
The phenomenon of juvenile misconduct, such as fighting and truancy, indicates a deficiency in religious values among students, reflected in the imbalance of emotional and intellectual intelligence influenced by spirituality. This study addresses the issue by implementing a constructivist approach, requiring students to actively engage and independently construct knowledge, enhancing retention. The research aims to examine the implementation of the constructivist approach in Islamic Religious Education (PAI) and its impact on student participation and understanding of religious values. Employing a qualitative descriptive methodology, this study investigates the effectiveness of the constructivist approach in improving student engagement and comprehension in PAI. Key findings indicate that the constructivist approach significantly enhances both student participation and understanding of religious values. These results imply that integrating constructivist methods in PAI can foster a more profound and lasting understanding of religious teachings among students.